Measuring tactile cues at the fingerpad for object compliances harder and softer than the skin - Hauser, Steven C. (IEEE Haptics Symp, 2016)
Distinguishing an object’s compliance, into percepts of “softness” and “hardness,” is crucial to our ability to grasp and manipulate it. Biomechanical cues at the skin’s surface such as contact area and force rate have been thought to help encode compliance. However, no one has directly measured contact area with compliant materials, and few studies have considered compliances softer than the fingerpad. Herein, we developed a novel method to precisely measure the area in contact between compliant stimuli and the fingerpad, at given levels of force and displacement. To determine the method’s robustness, we conducted psychophysical and biomechanical experiments with human subjects. The results indicate that cues including contact area at stimulus peak force of 3 Newtons, force rate over stimulus movement and at peak force, displacement and/or time to reach peak force may help in discriminating compliances while the directional spread of contact area is less important. Between softer and harder compliances, some cues were slightly more evident, though not yet definitively. Based upon the method’s utility, the next step is to conduct broader experiments to distill the mixture of cues that encode compliance. The importance of such work lies in building haptic displays, for example, to render virtual tissues.